Aristotele’s teaching on truth - Bańka, Jakub Sebastian (Folia Philosophica, 2000)
The purpose of the prior philosophy is to examine being as being. The latter takes multiple forms owing to the categories of actuality vs. possibility, and truth vs. falsehood. Each of these interpretations of being shows some of it. but they together disguise it under the multiplicity of possible descriptions. Being as truth, however, is singled out, which means that, for the sake of this interpretation, other senses of being will form a unity of its understanding. The dianoetic truth, indirectly connected with being thought of according to the categories, has, however, its basis in the noetic truth, that is in one that elicits no contradictory statement. In this way. it is from the noetic truth that the dianoetic one is derived, that is one that lends itself to interpretation according to the categories, and expresses the essential and contingent, possible and actual being. The ultimate possibility of understanding the multiple being with reference to unity is based then on the noetic interpretation of being as what is. In this way, the categories applied to substance can be understood both in an ontic way (as schemes of being), and in a logical way (as schemes of predication), because such distinctions are only the results of an analysis of the original ontological unity of the categorial synthesis the source of which is in the noetic cognition.